Comparing Deep Reinforcement Learning Algorithms’ Ability to Safely Navigate Challenging Waters - Larsen, Thomas Nakken; Teigen, Halvor Ødegård; Laache, Torkel; Varagnolo, Damiano; Rasheed, Adil (Frontiers in Robotics and AI, 2021)
Reinforcement Learning (RL) controllers have proved to effectively tackle the dual objectives of path following and collision avoidance. However, it is not necessarily easy to find which RL algorithm setup optimally trades off these two tasks. This work proposes a methodology to explore this that leverages analyzing the performance and task-specific behavioral characteristics for a range of RL algorithms applied to path-following and collision-avoidance for underactuated surface vehicles in environments of increasing complexity. Compared to the introduced RL algorithms, the results show that the Proximal Policy Optimization (PPO) algorithm exhibits superior robustness to changes in the environment complexity, the reward function, and when generalized to environments with a considerable domain gap from the training environment. Whereas the proposed reward function significantly improves the competing algorithms' ability to solve the training environment, an unexpected consequence of the dimensionality reduction in the sensor suite, combined with the domain gap, is identified as the source of their impaired generalization performance.